Functional reconstitution of the lysosomal sialic acid carrier into proteoliposomes. - Mancini, G M (1992)
The lysosomal carrier for the acidic monosaccharides sialic acid and glucuronic acid was solubilized from rat liver lysosomal membranes and reconstituted into phospholipid vesicles. Membrane proteins were extracted from lysosomal membranes with Triton X-100. Upon removal of the detergent by absorption on Amberlite XAD-2 beads, the solubilized proteins were incorporated in egg yolk phospholipids. The reconstituted proteoliposomes show proton-driven carrier-mediated uptake of acidic monosaccharides. The reconstituted carrier was compared in several characteristics with the transporter as present in the native lysosomal membrane. Transporter substrate affinity (Kt for glucuronic acid = 0.4 mM) and specificity for acidic monosaccharides are completely retained. The proteoliposomes also demonstrate trans-stimulation properties with both substrates sialic acid and glucuronic acid. The transporter is inhibited, both in its native and in the reconstituted state, by the sulfhydryl-modifying agents p-chloromercuribenzoic acid, N-ethylmaleimide, and phenyl isothiocyanate. In native membrane vesicles, arginine and histidine modifiers phenylglyoxal and diethyl pyrocarbonate inactivated transport in a substrate-protectable manner. In reconstituted proteoliposomes, similar inhibition was observed. However, protection by substrates was achieved only after treatment with phenylglyoxal. These data suggest that arginine or histidine residues or both are present at or near the substrate binding site of the carrier. Possibly, other essential histidines become exposed in the reconstituted state. The successful functional reconstitution of the lysosomal sialic acid carrier represents an important step towards its purification and its detailed molecular characterization.